1994
DOI: 10.1182/blood.v84.11.3724.bloodjournal84113724
|View full text |Cite
|
Sign up to set email alerts
|

Platelet adhesion to fibronectin in flow: dependence on surface concentration and shear rate, role of platelet membrane glycoproteins GP IIb/IIIa and VLA-5, and inhibition by heparin

Abstract: Platelet adhesion to purified surface-immobilized fibronectin under flow conditions was investigated. Fibronectin was found to support attachment and spreading of platelets. The extent of platelet spreading depended on the amount of immobilized fibronectin. An antiglycoprotein (anti-GP) IIb/IIIa antibody and an Arg-Gly-Asp (RGD)-containing peptide inhibited adhesion almost completely, whereas antibodies directed against platelet GP Ic/IIa (very late antigen 5) inhibited by 50%. Similar results with the antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
38
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(45 citation statements)
references
References 44 publications
5
38
0
Order By: Relevance
“…Another characteristic of fibronectin and fibrinogen is that both these proteins are capable of capturing platelets under flow conditions [28,29]. In our hands, fibrinogen was the strongest platelet adhesive surface under both arterial and venous shear rates.…”
Section: Discussionsupporting
confidence: 54%
“…Another characteristic of fibronectin and fibrinogen is that both these proteins are capable of capturing platelets under flow conditions [28,29]. In our hands, fibrinogen was the strongest platelet adhesive surface under both arterial and venous shear rates.…”
Section: Discussionsupporting
confidence: 54%
“…Antibodies against the VWF GPIb binding site inhibited platelet adhesion to TSP-1 at 1600 s -1 and 1700 s -1 to ~30%. Unlike platelet adhesion to fibronectin (27), platelet mediated adhesion to TSP-1 does not depend on VWF.…”
Section: Discussionmentioning
confidence: 87%
“…They suggested that fibronectin from the α-granules might be the ligand. However, platelet adhesion to fibronectin has an optimum at 300 s -1 (27) and, at arteriole shear rates, platelets do not adhere to fibronectin. TSP-1 is a much better candidate to promote thrombus formation in coronary or cerebral arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Standard platelet aggregometry ( Kirlough‐Ratbone et al , 1983 ) is limited to platelet counts above 100.0 × 10 9 /l and its application to risk assessment among thrombocytopenic patients is therefore limited. Standard bleeding time is poorly standardized and has major practical limitations ( Rodgers & Levin, 1991), and other recently described methods of testing platelet function have not yet proved their clinical applicability ( Michelson, 1996; Ikeda et al , 1991 ; Beumer et al , 1994 ; Baumgartner, 1974; Diaz‐Ricart et al , 1994 ; Kundu et al , 1995 ; Mammen et al , 1990 ).…”
mentioning
confidence: 99%